Revelation as the foundation of social reality: a paradigm of divine constructed reality - Jamil, Farooqui (IIUM Press, 2015)
The dominant premise in social sciences in general and in sociology of knowledge in particular is that the reality of everyday life depends upon socio-cultural condition and historicity of a society. In other word, it is socially constructed. There are two monumental works: Peter Berger and Thomas Luckmann's The Social Construction of Reality, 1967 and John R. Searle's The Construction of Social Reality, 1995. They advocate that the reality is based on what the majority of people or society believes. It, further indicates that peoples' perceptions of reality differ and there is no way to prove that one reality is more correct that the other (A. Henderson, 1995). Thus, the social construction of reality is used to give a common ground of communication that unites the perception of reality among those who want to communicate effectively. The paper observes that this notion of reality and its construction is defective as it is not linked with truth and goodness. The social reality is the manifestation of some cardinal principles revealed by the Absolute Reality, which is the source and epitome of truth and goodness (Wallerstein, 1976). Those principles enable human to lead a peaceful, harmonious and successful life in the world. They are in the best interest of humanity and thus altruistic. As the revelation comes from Divinity, so the society is formed and shaped by Divine guidance. Humans' struggle of existence and to act and behave in dayto-day life is shaped by the Divine guidance. Hence, the reality that emerges is Divine constructed reality.